Pelaksannan Tu Ngawu (Antar Belis) dan Akibatnya dalam Perkawinan Adat pada Masyarakat Adat Roworeke, Kabupaten Ende (Dialektika Antara Idealitas dan Realitas) - Balduinus Rasi Mbedhi; Darius Mauritius; Husni Kusuma Dinata (Jurnal Hukum dan Sosial Politik, 2024)
Belis is as a form of appreciation, or honor to the woman and her family, belis This also serves as a bond in the marital relationship, belis Having a marriage certification tool is a symbol of a woman's status with economic, social, and moral functions, and symbolizes femininity, belis also holds a very important meaning in traditional marriage. The main issue in this study are: (1) what is the process of determining belis and implemantion between belis in traditional marriages among the Roworeke indigenous community, Ende District (2) What are the legal consequences of between dowries in traditional marriages among the Roworeke indigenous community, Ende District? The research method used in this research is Juridical Empirical research, which means that in analyzing the problems it is done by combining legal materials (which are secondary data) with primary data obtained in the field. The legal sources and materials used are primary, secondary and tertiary legal materials. The results of this study indicate (1) what is the process of determining belis and implemantion between belis in traditional marriages among the Roworeke indigenous community, Ende District (2) The legal consequences that occur when belis is carried out fully, partially, and not at all.